Predictability of Job Satisfaction and Self-esteem on Organisational Commitment among Non-academic Staff - Ehondor, Esohe G.; Ayoola, Olufemi A.; Uye, Emmanuel E. (International Journal of Multidisciplinary Approach Research and Science, 2025)
Organisational commitment remains the backbone of growth and development in for-profit and nonprofit organisations. However, studies investigating organisational commitment in educational sectors have produced different results. Therefore, this study examined the predictability of job satisfaction and self-esteem on organisational commitment among non-academic staff in a Nigerian federal university. A cross-sectional survey research design was adopted, a purposive sampling technique was used to select one federal University, and a convenience sampling technique was used to select participants to administer the questionnaires. Data were collected from 292 participants using validated scales and analysed using independent samples t-test and multiple regression analysis. At the same time, the hypotheses tested were accepted at a p < .05 level of significance. The result revealed that job satisfaction and self-esteem jointly predicted organisational commitment among study participants [R2 = .05, F (2,291) =7.37, p < .05]. Moreover, the results showed that job satisfaction independently predicted organisational commitment among study participants (β =.22, p <.05). However, self-esteem did not independently predict organisational commitment among study participants (β =.08, p >.05]. The study concluded that job satisfaction more than self-esteem tends to predict organisational commitment among study participants strongly. It is recommended that human resources planning units in higher institutions should put in place robust programmes that would enhance organisational commitment among their employees.